2017
DOI: 10.2147/ppa.s128658
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the exit knowledge of patients for dispensed drugs at outpatient pharmacy of Hiwot Fana Specialized University Hospital, Eastern Ethiopia

Abstract: BackgroundA satisfactory counseling process between the patient and pharmacist is critical for rational use of dispensed drug(s) and is highly influenced by many factors including the experience of pharmacist in dispensing process. To improve patients’ knowledge of dispensed drugs, it is necessary to understand the factors that optimize a pharmacist interaction with a patient in each activity of the dispensing process. Therefore, the aim of this study was to identify the pharmacist and patient factors that inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 20 publications
3
31
0
5
Order By: Relevance
“…The most effective tasks in promoting the pharmacist–patient interaction were obtaining patients' history and provision of verbal instruction. Besides, eye contact was significantly related to patient perceptions of clinician empathy and connectedness ( 28 30 ). However, very short dispensing time was considered as a major factor for inadequate provision of medication counseling and hence results in poor exit knowledge of patients about their dispensed drugs ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most effective tasks in promoting the pharmacist–patient interaction were obtaining patients' history and provision of verbal instruction. Besides, eye contact was significantly related to patient perceptions of clinician empathy and connectedness ( 28 30 ). However, very short dispensing time was considered as a major factor for inadequate provision of medication counseling and hence results in poor exit knowledge of patients about their dispensed drugs ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, perception of outpatients about the technical knowledge of pharmacists was also indicated to independently affect their satisfaction and quality of the patient–pharmacist interactions ( Alghurair et al, 2012 ). Patients who perceived instruction and politeness of pharmacists as satisfactory and positive, respectively, were identified to have good knowledge for dispensed medications at exit from outpatient pharmacy of HFSUH ( Hirko and Edessa, 2017 ). This study had investigated perception of outpatients pertaining to knowledge of pharmacists about medications they are dispensing and their communication; however, it did not measure ethnicity and language of preference for the pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The interview was made by using a structured questionnaire that involves satisfaction questions customized from the World Health Organization (WHO) criteria for satisfaction of pharmaceutical service provisions ( FMHACA, 2012 ; MSH, 2012 ). A complete data for a questionnaire designed to assess patients’ perceived interaction status with pharmacists and other parameters aimed to assess factors influencing the exit knowledge of the patients for dispensed medicines was fully indicated in a previous publication that partly used the same dataset obtained from interview of patients served at HFSUH ( Hirko and Edessa, 2017 ). However, data addressing satisfaction of patients with the pharmacy services at the two hospitals were not included in the previous publication.…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, in Botswana Boonstra and co-workers [ 2 ] looked at labelling and knowledge of dispensed drugs as quality indicators in primary care and found that patients had a reasonable knowledge of medicines but that family welfare educators did not. In Ethiopia Hirko and Edessa [ 10 ] explored the exit knowledge of patients at an outpatient pharmacy from a university hospital. From 422 respondents, they found that the majority of patients poorly understood the name of the dispensed medication, side effects and what to do with missed doses.…”
Section: Introductionmentioning
confidence: 99%